2018
DOI: 10.5194/npg-25-129-2018
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating assimilation development for new observing systems using EFSO

Abstract: Abstract. To successfully assimilate data from a new observing system, it is necessary to develop appropriate data selection strategies, assimilating only the generally useful data. This development work is usually done by trial and error using observing system experiments (OSEs), which are very time and resource consuming. This study proposes a new, efficient methodology to accelerate the development using ensemble forecast sensitivity to observations (EFSO). First, non-cycled assimilation of the new observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…In this paper, we aim to explore the impact of cycling PQC using an intermediate complexity system to act as a bridge between the promising results obtained in CK19 using the simple Lorenz (1996) model and a full operational system. For this purpose, we use the GFS-LETKF system developed by Lien et al (2016), which reduces the complexity of the DA system and uses a lower resolution of the spectral GFS model (compared to the operational systems) in order to expedite the execution of the experiments while still using a realistic configuration of a forecasting model, data assimilation system, and observations. The underlying philosophy behind the design of the GFS-LETKF system is to have a simple configuration of a DA system coupled with the realistic spectral GFS model to allow fast experiments exploring innovative data assimilation techniques.…”
Section: Experimental Design a Da System Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we aim to explore the impact of cycling PQC using an intermediate complexity system to act as a bridge between the promising results obtained in CK19 using the simple Lorenz (1996) model and a full operational system. For this purpose, we use the GFS-LETKF system developed by Lien et al (2016), which reduces the complexity of the DA system and uses a lower resolution of the spectral GFS model (compared to the operational systems) in order to expedite the execution of the experiments while still using a realistic configuration of a forecasting model, data assimilation system, and observations. The underlying philosophy behind the design of the GFS-LETKF system is to have a simple configuration of a DA system coupled with the realistic spectral GFS model to allow fast experiments exploring innovative data assimilation techniques.…”
Section: Experimental Design a Da System Configurationmentioning
confidence: 99%
“…Other studies have explored the applications of FSO impacts. It was shown in Lien et al (2018) that the longterm-averaged EFSO impact provides detailed information for optimizing data selection and the design of quality control procedures. Kotsuki et al (2017) found that using EFSO impact as an ordering method in a serial ensemble square root filter for the Lorenz (1996) model significantly improved the analysis accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hotta et al (, hereafter H17) proposed a proactive quality control method (PQC) that detects detrimental observations with the EFSO. Lien et al () proposed an efficient approach to assimilating a new observing system using the EFSO. Recently, Buehner et al () proposed a new hybrid FSO, in which DA uses the adjoint model and FSO employs ensemble forecasts, for a hybrid ensemble‐variational data assimilation system.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent analysis fields of DA systems (hereafter, subsequent analyses) are usually used as the reference. It is also possible to use analysis fields from other DA systems as the reference (Lien et al , ). Recently, Todling () proposed using observation departures (i.e.…”
Section: Introductionmentioning
confidence: 99%